Digi - Insurance – the Case Story of the Potential in the Life Insurance of Sri Lanka - Paranavitana, Suresh (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2023)
This study aims to see how insurance products are developed by life insurance companies operating in Sri Lanka, providing products that are acceptable in the markets where they operate. The essence of this paper is to highlight the ability of direct communication between the insured and the insurer through digital transformation and in facilitating direct (premium payment) transactions between the insured and the insurer through their respective banks. This research uses qualitative research methods with descriptive methods. The research results show that insurance plays a major role in developing life insurance products and is a liaison between the insurer and the insured and in certain cases a facilitator to collect premiums on behalf of the insurer. Keywords: Brand Communication; Digital Transformation; Insurance Industry Sri Lanka; Life Insurance; Linking Insured and Insurer; Marketing Communication Abstrak This study aims to see how insurance products are developed by life insurance companies operating in Sri Lanka, providing products that are acceptable in the markets where they operate. The essence of this paper is to highlight the ability of direct communication between the insured and the insurer through digital transformation and in facilitating direct (premium payment) transactions between the insured and the insurer through their respective banks. This research uses qualitative research methods with descriptive methods. The research results show that insurance plays a major role in developing life insurance products and is a liaison between the insurer and the insured and in certain cases a facilitator to collect premiums on behalf of the insurer. Kata Kunci: Komunikasi Merek; Transformasi Digital; Industri Asuransi Sri Lanka; Asuransi Jiwa; Menghubungkan Tertanggung Dan Penanggung; Komunikasi Pemasaran